Church Missionary Society archive (Adam Matthew Publications, 2002)
Reproduces original papers, held partly at CMS Headquarters in London and also at the University of Birmingham, consisting of letters, journals and papers of individual missionaries and catechists, providing a wide variety of information on mission work, schools and medical work in India.